Bismuth Tribromide Catalyzed Oxidation of Alcohols with Aqueous Hydrogen Peroxide - Han, Mi-kyung; Kim, Sohwa; Kim, Sung Tae; Lee, Jong Chan (Synlett, 2015)
An efficient bismuth tribromide catalyzed oxidation of various alcohols with aqueous hydrogen peroxide is described, leading to the corresponding carbonyl compounds.
Keywords: alcohols; catalysis; green chemistry; oxidation; hydrogen peroxide